PENGARUH KEPEMIMPINAN, KARAKTERISTIK BIOGRAFIS, DAN MOTIVASI TERHADAP KINERJA OPERATOR PROSES PT. SUGAR LABINTA LAMPUNG SELATAN - Hana Siti Hanifah; Wuryaningsih Dwi Sayekti; Adia Nugraha (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2022)
This study aims to analyze the leadership, background, and motivational impact of process operator leadership, motivation, and performance and processing operator performance.  This survey was conducted at PT Sugar Rabinta South Lampung, especially the processing unit in December 2021 to January 2022.  This research is conducted by a survey method involving 63 samples of processing operators.  Respondents in this study are foreman and operators.  The survey data were analyzed using descriptive analysis and multiple linear regression analysis.  The results showed that the foreman leadership of the processing section were quite good, the motivation of processing operators was quite good and the performance of process operators was categorized as good.  Ethnicity had a significant effect on the performance of process operators, while age, education, length of service, and the number of family members had no effect on the performance operators.  Leadership and motivation had significant effect on the performance of process operators.Key words: biographical characteristics, employee performance, motivation, leadership